Efektivitas mengkonsumsi minuman mengandung kafein saat berkendara - Parvez, Sabita Lutfun Nisa Ramdhini (Maliki Interdisciplinary Journal, 2023)
Caffeine is a natural substance found in coffee, tea and chocolate. Coffee can reduce fatigue and drowsiness so that it can increase energy when doing activities. The purpose of this study was to determine the effectiveness of consuming caffeinated drinks while driving. This type of research is a literature review or literature review from various collections of data sources related to the discussion in this study from journals, books, theses, the internet and other literature. This method will provide updated factual information from 2018-2023 from a review of the appropriate literature after which the results are compared in an article. The results of this study indicate that consuming caffeinated drinks while driving is considered effective as long as it is not consumed excessively in both adolescents and adults. Consuming caffeinated drinks can improve driving safety by maintaining vigilance when driving long distances or when drivers are tired so that there is no danger due to fatigue and drowsiness so that they can increase the body's energy in carrying out daily activities.